Alternative distribution to estimate the Dose – Response model in bioassay excrement - رشيد, ظافر حسين; الدوري, انتصار عريبي (Journal of Economics and Administrative Sciences, 2007)
Alternative  distribution  to estimate the Dose – Response  model in bioassay  excrementThis research   concern to study five different distribution (Probit , Logistic, Arc sine , extreme value , One hit  ), to estimate  dose –response model by using m.l.e  and probit method This is done by determining different  weights in each  distribution in addition find all particular statistics for vital model .